Effect of rate and time of nitrogen application on growth and yield of turmeric (Curcuma longa L.) - Saini, B S Gill, R Krorya, K N Sharma, S S (Journal of Spices and Aromatic Crops, 2001)
An experiment was conducted to study the response of turmeric to rate and time of N application. The treatments consisted of three levels of nitrogen (60, 120 and 180 kg ha-1) as main plot treatments and number of applications (nitrogen applied in equal splits of one, two, three, four and five) as sub-plot treatments. The results showed that 60 kg N ha-1 produced maximum fresh rhizome yield. Turmeric yield at 60, 120 and 180 kg N ha-1 did not differ significantly. Nitrogen applied in three equal splits produced maximum fresh rhizome yield and it was significantly superior to application of whole N at planting and in two splits. N content in leaf, rhizome and available nitrogen in soil increased with increase in the level of nitrogen and number of split application.